2015 Gout Classification Criteria: An American College of Rheumatology/European League Against Rheumatism Collaborative Initiative. Issue 10 (9th September 2015) - Neogi, Tuhina; Jansen, Tim L. Th. A.; Dalbeth, Nicola; Fransen, Jaap; Schumacher, H. Ralph; Berendsen, Dianne; Brown, Melanie; Choi, Hyon; Edwards, N. Lawrence; Janssens, Hein J. E. M.; Lioté, Frédéric; Naden, Raymond P.; et al.
Abstract : Objective: Existing criteria for the classification of gout have suboptimal sensitivity and/or specificity, and were developed at a time when advanced imaging was not available. The current effort was undertaken to develop new classification criteria for gout. Methods: An international group of investigators, supported by the American College of Rheumatology and the European League Against Rheumatism, conducted a systematic review of the literature on advanced imaging of gout, a diagnostic study in which the presence of monosodium urate monohydrate (MSU) crystals in synovial fluid or tophus was the gold standard, a ranking exercise of paper patient cases, and a multicriterion decision analysis exercise. These data formed the basis for developing the classification criteria, which were tested in an independent data set. Results: The entry criterion for the new classification criteria requires the occurrence of at least 1 episode of peripheral joint or bursal swelling, pain, or tenderness. The presence of MSU crystals in a symptomatic joint/bursa (i.e., synovial fluid) or in a tophus is a sufficient criterion for classification of the subject as having gout, and does not require further scoring. The domains of the new classification criteria include clinical (pattern of joint/bursa involvement, characteristics and time course of symptomatic episodes), laboratory (serum urate, MSU‐negative synovial fluid aspirate), and imaging (double‐contour sign on ultrasound or urate on dual‐energy computed tomography, radiographic gout‐related erosion). The sensitivity and specificity of the criteria are high (92% and 89%, respectively). Conclusion: The new classification criteria, developed using a data‐driven and decision analytic approach, have excellent performance characteristics and incorporate current state‐of‐the‐art evidence regarding gout.